Engaging art : essays and interviews from around the globe - Bernstein, Roslyn (Cambridge Scholars Publishing, 2020)
This book explores the tangled texture of the art world, a curious and mysterious space. In 60 essays, drawn from around the globe, it reveals new dimensions about how artists make their art, resist censorship and retain an independent, creative spirit. The essays ask and answer several crucial questions: How do artists in Europe, the United States, Asia, the Middle East, and Latin and South America find space to live and work? How do artists follow their talent to make and exhibit original art in a politicized world where artistic freedom is often limited? How do smaller artistic venues surviv.